1990
DOI: 10.1021/j100369a018
|View full text |Cite
|
Sign up to set email alerts
|

Laser spectroscopic and quantum chemical studies of the lowest excited states of formic acid

Abstract: 50) Eberhardt, W.; Sham, T. K.; Carr, R.; Krummacher, S.; Strongin, M.; Weng, S. L.; Wesner, D. A fluorescence excitation spectrum of formic acid monomer (HCOOH) has been recorded in the 268-257-nm region and has been attributed to an n -+ K* electron promotion in the anti conformer. The So -SI electronic origins of the HCOOH/HCOOD/DCOOH/DCOOD isotopomers were assigned to weak bands observed at 37 431.5/37 461.5/ 37 445.5/37 479.3 cm-I. Four vibrational modes, u3(c=o), v7(o-c=o), u8(C-HaId), and u9(0-Hh d), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
32
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 5 publications
8
32
0
Order By: Relevance
“…The lower energy region of the excitation spectra is identical to that previously reported.I6 One can readily assign the vibrational bands as shown in Figure 1 by using the assignment of the 00 band made by Ioannoni et a1. 16 and the progression analysis of Ng and Bell.20 The gradual rise of the broad background absorption appears to contribute little to the intensity of the excitation spectrum. Ng and Be1120 showed that the rotational contour of the 3; band (CO band in their notation) can be simulated by a mixture of A-, B-, and C-type transitions in the ratio of 1:1:2.…”
Section: Resultsmentioning
confidence: 99%
“…The lower energy region of the excitation spectra is identical to that previously reported.I6 One can readily assign the vibrational bands as shown in Figure 1 by using the assignment of the 00 band made by Ioannoni et a1. 16 and the progression analysis of Ng and Bell.20 The gradual rise of the broad background absorption appears to contribute little to the intensity of the excitation spectrum. Ng and Be1120 showed that the rotational contour of the 3; band (CO band in their notation) can be simulated by a mixture of A-, B-, and C-type transitions in the ratio of 1:1:2.…”
Section: Resultsmentioning
confidence: 99%
“…This same progression is observed to attach to a weak band at 404 cm Ϫ1 that has been attributed to a quantum addition of the O-CvO bending mode, Q 7 . 4 The identification of the CvO stretching mode, Q 3 , should be straightforward. However, the fluorescence emission breaks off very early on in the spectrum and band progressions at higher energies cannot be identified.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The following five dissociation channels are energetically possible after excitation within the S 1 ← S 0 absorption region: 8 deduced to occur after intersystem crossing ͑ISC͒ to the a 3 AЉ state. The absorption cross-section increases with decreasing wavelength and peaks near 210 nm.…”
Section: Introductionmentioning
confidence: 99%